(Re)designing programs : a vision for equity-centered, clinically based teacher preparation - Jacobs, Jennifer (Professor of education); Burns, Rebecca West (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"Given the increasing diversity of the United States and students entering schools, the value of teacher learning in clinical contexts, and the need to elevate the profession, national organizations have been calling for a re-envisioning of teacher preparation that turns teacher education upside down. This change will require PK-12 schools and universities to partner in robust ways to create strong professional learning experiences for aspiring teachers. University faculty, in particular, will not only need to work in schools, but they will need to work with schools in the preparation of future teachers. This collaboration will be equity- centered on addressing the inequities that PK-12 students face and working together to bring about greater equity and justice for our nation's students. The purpose of this book is to support individuals who are passionate about and interested in preparing teachers, in designing clinically based teacher preparation programs that place equity at the core and align with calls for transforming teacher education. Drawing from the literature as well as our experiences in designing and coordinating award-winning teacher education programs, we offer a vision for equity-centered, clinically based preparation that promotes powerful teacher professional learning and develops high-quality, equity-centered teachers for schools. The chapter topics include policy guidelines, partnerships, intentional clinical experiences, coherence, curriculum and coursework, university-based teacher educators, school-based teacher educators, supervision, the role of research, and instructional leadership in teacher preparation. While the concepts we share are research-based and grounded in the empirical literature, our primary intention is for this book to be of practical use. We hope that by the time you finish this book, you will feel inspired and equipped to make change within your own program, your institution, and your local context. We begin each chapter with a "Before You Read" section that includes introductory activities or self-assessment questions to prompt reflection about the current state of your teacher preparation program. We also weave examples, a "Spotlight from Practice," in the form of vignettes designed to spark your thinking for program improvement. Finally, we conclude each chapter with a section called "Exercises for Action," which are questions or activities to help you (re)imagine and move toward action in the (re)design of your teacher preparation program. We hope that you will use the exercises by yourself, but perhaps more importantly, with others to stimulate conversations about how you can build upon what you are already doing well to make your program even better"-- Provided by publisher.
Keywords: Teachers -- Training of -- United States.; Student teaching -- United States.; College-school cooperation -- United States.; Education -- Teacher Training & Certification.; Teacher training.; elektronické knihy; electronic books